New zircon data supporting models of short-lived igneous activity at 1.89 Ga in the western Skellefte District, central Fennoscandian Shield - Skyttä, Pietari; Hermansson, Tobias; Andersson, Jenny; Whitehouse, Martin; Weihed, Pär (Solid Earth, 2011)
New U-Th-Pb zircon data (SIMS) from three intrusive phases of the Palaeoproterozoic Viterliden intrusion in the western Skellefte District, central Fennoscandian Shield, dates igneous emplacement in a narrow time interval at about 1.89 Ga. A locally occurring quartz-plagioclase porphyritic tonalite, here dated at 1889 ± 3 Ma, is considered the youngest of the intrusive units, based on the new age data and field evidence. This supports an existing interpretation of its fault-controlled emplacement after intrusion of the dominating hornblende-tonalite units, in this study dated at 1892 ± 3 Ma. The Viterliden magmatism was synchronous with the oldest units of the Jörn type early-orogenic intrusions in the eastern part of the district (1.89–1.88 Ga; cf. Gonzàles Roldán, 2010). A U-Pb zircon age for a felsic metavolcanic rock from the hanging-wall to the Kristineberg VMS deposit, immediately south of the Viterliden intrusion, is constrained at 1883 ± 6 Ma in this study. It provides a minimum age for the Kristineberg ore deposit and suggests contemporaneous igneous/volcanic activity throughout the Skellefte District. Furthermore, it supports the view that the Skellefte Group defines a laterally continuous belt throughout this "ore district". Tentative correlation of the 1889 ± 3 Ma quartz-plagioclase porphyritic tonalite with the Kristineberg "mine porphyry" suggests that these units are coeval at about 1.89 Ga. Based on the new age determinations, the Viterliden intrusion may equally well have intruded into or locally acted as a basement for the ore-hosting Skellefte Group volcanic rocks. Godkänd; 2011; 20111123 (piesky)